2019
DOI: 10.1016/j.jcot.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection (UTI) at time of geriatric hip fracture surgery increases the risk of experiencing adverse 30-day outcomes

Abstract: Introduction: Pre-operative urinary tract infection (UTI) may be associated with a high rate of complications following surgeries. Few studies have investigated the clinical impact of a pre-operative UTI on post-operative outcomes following surgeries for hip-fracture in geriatric patients. Methods: The 2015e2016 ACS-NSQIP database was queried for patients undergoing hip fracture surgery using CPT-Codes for Total Hip Arthroplasty (27130), Hemiarthroplasty (27125) and Open Reduction/Internal Fixation (ORIF) (272… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…Other infections were also associated with the mortality risk in this population, such as urinary tract infections, which complies with findings of other studies that made this correlation with other complications similar to surgical site infection [18], such as progression to sepsis and extended hospital stay [57].…”
Section: Plos Onesupporting
confidence: 89%
“…Other infections were also associated with the mortality risk in this population, such as urinary tract infections, which complies with findings of other studies that made this correlation with other complications similar to surgical site infection [18], such as progression to sepsis and extended hospital stay [57].…”
Section: Plos Onesupporting
confidence: 89%
“…NSQIP PATOS variables were associated with increased complications and mortality. [21][22][23][24] However, the literature on preoperative acute conditions is limited with only select conditions studied for targeted surgeries. We found that although males had higher rates and aOR of PASC, males presenting with PASC had lower odds of mortality compared to females with PASC using both subgroup and interaction term analyses across a broad array of surgical types.…”
Section: Discussionmentioning
confidence: 99%
“…Frailty was assessed by the recalibrated and validated RAI 18,19,29 defining frailty categories as robust ( < 20), normal (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), frail (30)(31)(32)(33)(34)(35)(36)(37)(38)(39), and very frail (≥40). Cases missing any NSQIP variable needed to calculate the RAI were excluded from the analysis (see SDC, http://links.lww.com/SLA/D239).…”
Section: Expansion Of Ossmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection could affect the healing process by interrupting osteogenesis of osteoblast [ 13 ]. (3) A previous study showed that UTI increased the risk of longer hospitalization, more than 5 days in hip fracture [ 14 ]. However, there were no such data on the risk of adverse outcome of UTIs after pelvic fracture surgery in regards to the importance and necessity of these clinical circumstances.…”
Section: Introductionmentioning
confidence: 99%